Analyzing the Routes of the Arbaeen Pilgrimage: Guiding Visitors to the Shrine of Imam Al-Hussein (PBUH) - Abdulameer, Abeer H.; Sayyid, Baqer H.; Salman, Shatha A. (Iraqi Journal of Science, 2026)
The annual pilgrimage to the shrine of Imam Hussein (peace be upon him) is a significant event for Iraqi society. Millions of Iraqis from all walks of life converge on the holy city of Karbala each year on the 20th of the month of Safar. The sheer scale of such gatherings necessitates in-depth study. Various methodologies were employed in this field, including graph theory and network analysis, to determine the shortest routes pilgrims take from their governorates (places of residence) to the holy city of Karbala. All roads leading to the city are primary, secondary, international, and public transportation networks are considered. The objective is to identify the optimal route for the movement of large Crowds to ensure a safe, secure, and efficient journey that minimizes travel time and maximizes the convenience of pilgrims. The Iraqi province's road shapefile collection documents the complicated road networks within each province. The findings of this study could be used by relevant authorities to plan and provide necessary services along the identified route. A detailed analysis of the primary road network in the study area showed that most of the road network in the eastern, southern, and western governorates converges on a single main road. In contrast, the northern governorates have a more extensive road network. Consequently, the shortest route identified in this study primarily passes through the cities named.